2015
DOI: 10.1074/jbc.m114.588913
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Glutathione Redox Potential of HIV-1-infected Macrophages

Abstract: Background: Abnormal glutathione poise has been associated with HIV-1 infection; however, the underlying importance is unclear.Results: Measurement of glutathione-redox potential (EGSH) revealed higher capacity of latently infected cells to resist oxidative stress and apoptosis, whereas HIV-1 replication perturbed glutathione homeostasis.Conclusion: Dynamic changes in EGSH regulate HIV-1 persistence and reactivation.Significance: Glutathione-redox signaling plays a critical role in HIV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
103
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(117 citation statements)
references
References 83 publications
13
103
0
1
Order By: Relevance
“…MBB reacts nonenzymatically with GSH and binds to thiol groups, and it is excited by UV light and then emits bluish fluorescence at 450 nm with an intensity that is proportional to the intracellular GSH content (35,36). GSH and GSSG levels were also measured using a glutathione assay kit as per the manufacturer's instructions (37). Briefly, 2 ϫ 10 7 cells from various experiments were collected in 500 l of cold 50 M MES buffer and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…MBB reacts nonenzymatically with GSH and binds to thiol groups, and it is excited by UV light and then emits bluish fluorescence at 450 nm with an intensity that is proportional to the intracellular GSH content (35,36). GSH and GSSG levels were also measured using a glutathione assay kit as per the manufacturer's instructions (37). Briefly, 2 ϫ 10 7 cells from various experiments were collected in 500 l of cold 50 M MES buffer and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Using a mitochondria-specific roGFP, Bhaskar et al showed that the values of E GSH are similar in the cytosol and mitochondria (~ −310 mV). 6 However, this measurement approached the detection limit of roGFP, which may underestimate the mGSH level. Additionally, E GSH is proportional to [GSH] 2 :[GSSG].…”
mentioning
confidence: 90%
“…Interestingly, transcription activation by exogenous hydrogen peroxide takes place only after the prolonged treatment, allowing us to hypothesize that virus-induced oxidative stress can play a crucial role in activation of the latent viral infection [138]. Supporting this, activation of the latent infection was triggered by modest changes in the cell redox potential (25 mV) [144]. Such changes can be induced either directly by HIV proteins or indirectly through the induction of proinflammatory cytokines such as TNF- α [145].…”
Section: Ros In Hiv's Life Cyclementioning
confidence: 99%